Hubungan Sosial Ketergantungan Nelayan Terhadap Tauke Di Desa Mantang Lama - Rahmawaty , Ratih; Pratama, Welfiandi Hedy; Apriadi , Robby; Sevriyansah , Toni; Ferdi, Ferdi; Wahyuni , Sri (CV. ITTC INDONESIA, 2024)
Indonesia is an archipelagic country. The possibility of an ideal abundance of fish can bring prosperity to the human life of a fisherman. However, in reality, this natural wealth cannot be obtained immediately by guaranteeing the creation of wealth for the lives of fishermen who live in coastal areas. Fishermen's dependence on tauke not only impacts economic transactions, but also impacts coastal communities. In this research, the author used a qualitative research method by collecting data, namely conducting interviews with fishermen regarding their dependence on tauke and conducting observations in Mantang Lama Village. From the results of the interview above in terms of facilities for worker fishermen to repair their own bots using capital from the tauke. This will also have an impact on the inseparability of working fishermen who are always tied to the tauke because of these things. One of the fishermen's dependence on tauke is borrowing money. Because the majority of fishermen in Mantang Lama Village do not have other jobs. Fishermen's dependence on tauke means they are trapped in complex patterns of cooperation. Starting from capital loans to production sharing agreements, these relationships create dependencies that are difficult for fishermen to break away from.